Homogeneous Palladium-Catalyzed Selective Reduction of 2,2′-Biphenols Using HCO2H as Hydrogen Source - Li, Ruoling; Li, Chenchen; Yang, Wen; Zhao, Wanxiang (Synthesis, 2021)
An efficient homogeneous palladium-catalyzed selective deoxygenation of 2,2′-biphenols by reduction of aryl triflates with HCO2H as the hydrogen source is reported. This protocol complements the current method based on heterogeneous Pd/C-catalyzed hydrogenation with hydrogen gas. This process provided the reduction products in good to excellent yields, which could be readily converted to various synthetically useful molecules, especially ligands for catalytic synthesis.
Keywords: palladium; homogeneous catalysis; 2,2′-biphenols; reduction; formic acid